Malaysian labour productivity for reinforced concrete structural frame: a case study - Ali, Maisarah; Abdul Hamid, Haslina; Idris , Mohd Zaifuddin (2012)
Abstract Labour productivity is one of the major tools in preparing an effective work program.As there is no principle on labour productivity being practiced in Malaysia for the preparation of work program, most of the construction planners are adopting the labour productivity data from other countries such as United Kingdom, United States. These labour productivity rates are unsuitable for Malaysian condition and frequently caused over-run in time and cost.The aim of the study is to come up with Malaysian labour productivity for reinforced concrete structural frame. Data were collected from two construction sites through observation and time study method. From the data calculations on labour productivity for reinforced concrete structural works were obtained. The study also came up with productivity equations which were derived from regression analysis.It is recommended that a more extensive data collection to be carried out in future studies to improve the accuracy of the data and the precision of the equations. Keywords Labour productivity, reinforced concrete structure, regression analysis, work program, construction planners